2022
DOI: 10.1002/eap.2648
|View full text |Cite
|
Sign up to set email alerts
|

Risky business: How an herbivore navigates spatiotemporal aspects of risk from competitors and predators

Abstract: Understanding factors that influence animal behavior is central to ecology.Basic principles of animal ecology imply that individuals should seek to maximize survival and reproduction, which means carefully weighing risk against reward. Decisions become increasingly complex and constrained, however, when risk is spatiotemporally variable. We advance a growing body of work in predator-prey behavior by evaluating novel questions where a prey species is confronted with multiple predators and a potential competitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 108 publications
1
15
0
Order By: Relevance
“…Although a 1‐km distance may be relatively coarse for identifying encounters with a stalk‐and‐ambush predator, we selected this distance in part not only due to sample size limitations but also so that we could test conventional methods of evaluating predator–prey encounters (e.g., Middleton et al, 2013). Encounters between two animals should be more likely to occur when both are active (Avgar et al, 2008; Scharf et al, 2006), and previous research in our study area indicated that activity curves for coyotes and mountain lions have a high degree of overlap (Huggler et al, in revision). Thus, while mountain lions use a more stationary hunting strategy than coyotes, they are unlikely to be entirely stationary in the time leading up to encounters.…”
Section: Methodssupporting
confidence: 53%
See 2 more Smart Citations
“…Although a 1‐km distance may be relatively coarse for identifying encounters with a stalk‐and‐ambush predator, we selected this distance in part not only due to sample size limitations but also so that we could test conventional methods of evaluating predator–prey encounters (e.g., Middleton et al, 2013). Encounters between two animals should be more likely to occur when both are active (Avgar et al, 2008; Scharf et al, 2006), and previous research in our study area indicated that activity curves for coyotes and mountain lions have a high degree of overlap (Huggler et al, in revision). Thus, while mountain lions use a more stationary hunting strategy than coyotes, they are unlikely to be entirely stationary in the time leading up to encounters.…”
Section: Methodssupporting
confidence: 53%
“…We used Random forest (RF) models (Breiman, 2001) to develop spatial predictions of probable mountain lion use (risk) and kill site occurrence (reward) across our study area (Huggler et al, in revision). We expanded on Huggler et al (in revision)’s models by including kill sites containing elk and pronghorn to characterize the full suite of ungulate kill sites. Random forest is a machine learning approach that combines many classification trees, does not rely on normality, and can readily incorporate interactions and variables that are correlated (Breiman, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed coyote use in each year they were collared to ensure that the majority of their locations (i.e., >85%) occurred within the study area and removed remaining coyote ID‐years with less than 500 locations within the study area. We used methods adapted from Ridout and Linkie (2009) and the overlap R package (Ridout & Linkie, 2009) to fit a kernel density function to coyote movement rates (meters per hour) and estimate peaks in activity when coyotes were most likely hunting (Huggler et al, 2022). We defined peaks in activity based on the times in which activity estimates were within 50% of the maximum (16:00–8:45 MST) and constrained our habitat selection analysis to this active period.…”
Section: Methodsmentioning
confidence: 99%
“…This crucial limitation can be solved by integrated step-selection analysis (iSSA), which allows simultaneous modelling of movement and habitat selection decisions by animals (Avgar et al , 2016), building upon the earlier technique of step selection analysis (SSA) (Fortin et al , 2005; Rhodes et al , 2005; Forester et al , 2009; Thurfjell et al , 2014). Not only has this fundamental methodological advancement lead to an explosion of the use of SSA and iSSA in recent years (Viana et al , 2018; Huggler et al , 2022; Northrup et al , 2022), and methodological extensions (Munden et al , 2021; Klappstein et al , 2021), but researchers have increasingly shown how the movement kernels parameterised during SSA can be ‘scaled-up’ to predict broader-scale space use patterns (Potts et al , 2014b; Avgar et al , 2016; Signer et al , 2017; Potts & Schlägel, 2020; Fieberg et al , 2021). Even though this markedly increases the level of understanding and the quality of predictions which can be obtained from animal movement analyses, such upscaling of step selection analysis is seldom done by the many studies using SSA, perhaps due to a lack of knowledge or perceived methodological difficulties.…”
Section: Introductionmentioning
confidence: 99%